OPTIMASI AEROELASTIK STRUKTUR SAYAP DENGAN METODA MODIFIED FEASIBLE DIRECTION - Haryanto, Ismoyo
Abstract : In aircraft structure design, the iterative process is needed in order to find the structure, which satisfy design requirements and mission. At the other hands, the missions of aeronautical vehicles of the future are becoming increasingly and, then, iterative process, which is based on traditionally/conventionally method, can not be economically applied anymore. Therefore, an optimisation procedure based on mathematical approach is necessary to be extensively applied. The basic principle of optimisation is to vary the design variables to met optimal objective function without violate the design constraints. One of the most important constraints in aircraft structure design is flutter because it will affect limitation of aircraft operation speed. In this research the optimisation of wing structure due to flutter constraint has been conducted. The structure is modelled as a stiffness beam and a mass beam, which are assumed rigidly connected each other and therefore there is no relatively movement between these beams. The quantity of unsteady aerodynamic load on wing is determined using strip theory based on Theodorsen formulae. Meanwhile flutter analysis is determined using PK method. The optimisation procedure is applied on the stiffness beam cross section by using modified feasible direction method (MFD). The results show that flutter is more sensitive due to change the width stiffness beam than its height. The other interesting result that is by using optimisation method the structure design based on given flutter speed can be done although as its consequence the structural mass will increase. Although in generally the results are satisfactory many improvements, such as application of approximation method and analytical method in sensitivity design analysis in order to reduce computational time are necessary.